Analyse des Sicherheitsgewinns durch Teilautomation am Beispiel eines Stauassistenten - Wulf, Felix (KIT Scientific Publishing, 2015)
In partially automated driver assistance systems it remains to the drivers to monitor the system's behavior on errors and to intervene in critical situations. It is the goal of the current research to further analyze the advantages and disadvantages of such systems. Within the exemplary situational context of partially automation in traffic-jams, new ways of interaction to enhance the drivers' ability to react to critical situations are derived and evaluated.